A tri-band frequency-selective surface - Mahaveer, Uttamchand (2022)
A novel low-profile tri-band bandpass frequency-selective surface (FSS) is proposed in this paper. The structure is designed by the two-dimensional repetition of a unit cell consisting of four apertures. Each aperture is a combination of T-shaped, U-shaped and a rectangular-shaped aperture aligned horizontally or vertically. The performance of the designed FSS structure is independent of the angle of incidence of the incident wave due to the orientation of the apertures in the unit cell. The designed FSS structure operates at the desired frequency bands close to 8-14 GHz. The insertion loss is close to 3.26, 2.68 and 1.12 dB at the respective frequencies of 8.1, 9.8 and 11 GHz. The advantage of this design is that it exhibits tri-band characteristics for various angles of incidence of the incident wave even though it is a low-profile single layer structure. The total dimensions of the unit cell are approximately 0.55 λ0 × 0.55 λ0 at 8 GHz.